Tver Gospel of 1478 (codicology and palaeography) - G.A. Nikolaev (Ученые записки Казанского университета: Серия Гуманитарные науки)
The codicological and paleographic description of the Tver Gospel of 1478, a dated Tetraevangelia manuscript, has been performed. The place and time of the manuscript creation are indicated in the copyist’s record at the end of the book (f. 322v.). The Gospel is kept in the Fund of Rare Books of the National Museum of the Republic of Tatarstan, no. 8772. It is a manuscript in quarto, 322 ff., written in the same handwriting, decorated with miniatures, initials, the tri-color medallions, etc. The text is well structured. The Gospels of the apostles are separated from each other by colored miniatures of the evangelists, made in the artistic manner of the Tver School of Painting. The manuscript is written in a clear half-text of the second half of the 15th century on paper with a “bull’s head” watermark. The book was restored in the late 18th century and is well preserved. The value of the dated and geographically confined texts to historical linguistics and culture, history of Church literature, etc. has been established.